Plant Signaling Peptides - Irving, Helen R.; Gehring, Chris (Signaling and Communication in Plants,, 2012)
Plants have evolved with a complex array of signaling molecules to facilitate their growth and development and their interactions with the environment.  A vast number of different peptide molecules form an important but until recently often overlooked component amongst these signaling molecules.  Plant peptide signals are involved in regulating meristem growth and organogenesis, modulating plant growth and homeostatic responses.  They also have important roles as signals of imminent danger or pathogen attack.  This volume focuses on the roles of various peptide signaling molecules in development, defence and homeostasis.  As it is likely that further plant peptide signaling molecules remain to be discovered, the last section takes a practical look at methods to identify new peptides and characterise their functions.